2009
DOI: 10.2215/cjn.05551008
|View full text |Cite
|
Sign up to set email alerts
|

Early Angiography in Patients with Chronic Kidney Disease

Abstract: Background and objectives: In the general population, an early invasive strategy of routine coronary angiography is superior to a conservative strategy of selective angiography in patients who are admitted with unstable angina or non-ST segment elevation myocardial infarction (MI), but the effectiveness of this strategy in individuals with chronic kidney disease (CKD) is uncertain.Design, setting, participants, & measurements: We conducted a collaborative meta-analysis with data provided by the main authors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 38 publications
5
78
1
Order By: Relevance
“…4,20,28 -31 Earlier studies have demonstrated the benefits of an early invasive strategy in ACS patients with CKD. 33 In the present study there were no significant differences in death or MI in patients with ACS, CKD, and elevated troponins treated with bivalirudin versus a heparin plus a GPI as part of an early invasive strategy (although a nonsignificant trend toward greater mortality with bivalirudin was present at 30 days that was absent at 1 year). Conversely, bivalirudin significantly reduced major hemorrhagic complications.…”
Section: Discussioncontrasting
confidence: 62%
“…4,20,28 -31 Earlier studies have demonstrated the benefits of an early invasive strategy in ACS patients with CKD. 33 In the present study there were no significant differences in death or MI in patients with ACS, CKD, and elevated troponins treated with bivalirudin versus a heparin plus a GPI as part of an early invasive strategy (although a nonsignificant trend toward greater mortality with bivalirudin was present at 30 days that was absent at 1 year). Conversely, bivalirudin significantly reduced major hemorrhagic complications.…”
Section: Discussioncontrasting
confidence: 62%
“…Cardiovascular disease is the leading cause of death among patients with moderate to severe renal dysfunction, 103 and early referral for revascularization may be beneficial in patients with suitable disease. 104 However, patients with underlying renal dysfunction are also at increased risk of complications after angiography and revascularization. [105][106][107] Unfortunately, as with diabetic patients, traditional relative MPI is unable to identify truly low-risk patients.…”
Section: Treatment Guidancementioning
confidence: 99%
“…In the highly validated GRACE risk score, serum creatinine is 1 of the 8 independent predictors of death. 945,969 In recent study, even early CKD constituted a significant risk factor for cardiovascular events and death. 971,972 Chronic kidney disease also predicts an increase in recurrent cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%